PENGEMBANGAN ALAT PENILAIAN PEMBELAJARAN MENYIMAK EKSPOSISI KELAS X SMA - Ary Fawzi Fawzi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2016)
The purpose of this study is to develop assessment tools for teaching and learning process and products in listening skills grade X senior high school. The products of the assessments include interactive and manual covering the tools to assess the teaching and learning process and products which include a dialogue journal and questionnaire. This study was adapted from research and development model from Djaali and Puji Mulyono. Based on the result of the tryout, the assessment products are valid for both its content and construct validity, reliable, practical, applicable and attractive. Consequently, the result of the revision is feasible to be implemented Permalink/DOI: dx.doi.org/10.17977/um015v44i22016p125